TRENDS IN UNICOMPARTMENTAL KNEE ARTHROPLASTY - Ahmet Nadir Aydemir; Mehmet Yucens (Acta Ortopédica Brasileira, 2020)
ABSTRACT Objective: To evaluate trends in publications on unicompartmental knee arthroplasty (UKA) from the past to the present. Methods: As a web-based analysis, all UKA research articles, editorial letters, case reports, reviews and meeting abstracts published on the Thomson Reuters’ Web of Knowledge were evaluated. The period from the first publication in 1980 to January 2019 was divided into four decades and publications were evaluated. Research articles were grouped into headings according to the subjects. Results: A total of 1,658 publications were evaluated in this study. The most frequent term used in the publications title was “outcome,” with 260 items, followed by “biomechanics and kinematics,” with 99 items. Most reports have been published in the last decade, and the most common type of publication was postoperative follow-up and results. Conclusion: In parallel with technological advancements, publications related to UKA-especially patient-specific instrumentation, navigation, and robotic surgery-will increase in number and become more specific. Level of Evidence V, Expert Opinion.